2015
DOI: 10.1002/cpa.21625
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Simon‐Wolff Spectral Criterion and Resonant Delocalization

Abstract: Discussed here are criteria for the existence of continuous components in the spectra of operators with random potential. First, the essential condition for the Simon-Wolff criterion is shown to be measurable at infinity. By implication, for the iid case and more generally potentials with the K-property the criterion is boosted by a zero-one law. The boosted criterion, combined with tunneling estimates, is then applied for sufficiency conditions for the presence of continuous spectrum for random Schrödinger op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In the Anderson tight binding model, which is the rank one case, Barry Simon [16] showed that any standard basis vector δ n is cyclic in region of pure point spectrum. Other works in pure point regime are by Klein-Molchanov [10] and Aizenman-Warzel [2]. Jakšić-Last in [7,9] showed that the singular spectrum is almost surely simple in case of Anderson type Hamiltonians where rank of the perturbation is one.…”
Section: Introductionmentioning
confidence: 99%
“…In the Anderson tight binding model, which is the rank one case, Barry Simon [16] showed that any standard basis vector δ n is cyclic in region of pure point spectrum. Other works in pure point regime are by Klein-Molchanov [10] and Aizenman-Warzel [2]. Jakšić-Last in [7,9] showed that the singular spectrum is almost surely simple in case of Anderson type Hamiltonians where rank of the perturbation is one.…”
Section: Introductionmentioning
confidence: 99%